Critical Mass, Social Networks and Collective Action: Exploring Student Political Worlds - Crossley, Nick; Ibrahim, Joseph (Sociology, 2012)
This article explores the role of ‘critical mass’ and social networks in the generation of collective action. Drawing on qualitative and quantitative (social network) data, the article argues that both are pivotal in the process whereby collective action takes shape. The empirical focus of the article is student politics but it is argued that the mechanisms and dynamics identified have a much wider domain of application.
Keywords: Social network analysis; campus politics; mixed methods; political recruitment; social cohesion; social worlds